STRATEGIC IMPROVING ACADEMIC ACHIEVEMENT THROUGH STRATEGIC MANAGEMENT : A CASE STUDY OF MADRASAH ALIYAH DARUSSALAM PARMERAAN - Sonang Pohan, Saima; Abdurrahman; Muhammad Rifa'i (Pena Cendekia Insani, 2025)
This study aims to analyze the strategic management of the head of Madrasah Aliyah Private Darussalam Parmeraan in improving students' academic achievement, which includes aspects of planning, implementation, and evaluation of strategies. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews, observations, and documentation involving madrasah heads, curriculum leaders, teachers, and students. The results of the study show that strategy planning is carried out in a visionary, collaborative, and based on mapping students' potential. The head of the madrasah prepares programs based on the interests and talents of students that are integrated in academic and religious activities. This process is in line with George R. Terry's theory of strategic planning and Bryson's model which emphasizes participation and identification of the internal and external environment. In the implementation stage, the head of the madrasah shows active leadership in organizing resources, shaping policies, and building an organizational culture that supports the implementation of strategies. Programs such as enrichment, remedial, teacher training, and Olympic coaching are carried out with strong coordination between the head of the madrasah and all educators. This reflects the principles of implementation strategy according to Fred R. David which underlines the importance of organizational structure, division of roles, and effective communication. At the evaluation stage, the head of the madrasah implements a systematic and participatory review mechanism through regular meetings, academic supervision, and study forums. The evaluation was carried out based on student and teacher performance data, with follow-up in the form of remedial programs and teacher professional development. This approach is not only a control, but also a means of organizational learning. Thus, the management strategy carried out by the head of the madrasah shows consistency and effectiveness in encouraging the continuous improvement of students' academic achievement.